Evaluating the Growth Performance and Mortality in Pre-Weaning Burmese Piglets Reared under Field Condition of Aizawl, India - C. Lalremruata; Joy Lalmuanpuia; T. Vanlalngurzauva (Research Advances and Challenges in Agricultural Sciences Vol. 5, 2024)
The highest tribal population of Mizoram among the North Eastern states is one of the reasons for the high demand for pork in the state. Large White Yorkshire, Hampshire, Mizo local and their crossbreds could not suffice the demand in the state so rearing of Burmese pigs gained popularity. The studies on the growth performance and mortality of Burmese piglets were conducted under the field conditions in Aizawl district of Mizoram. The data of 35 male and 40 female piglets were studied for a period of 11 months (July 2009 to May 2010). The result revealed that sex had a significant effect (P<0.05) on piglet body weight from birth till 8th week, males had higher body weight at all ages than females however the fortnightly body weight gain was higher in females than males; 155.85 gm and 168.60±0.01 gm in male and female respectively. For both male and females, fortnightly body weight gain increased from FN1 to FN2, however, it declined from FN3 to FN4. Pre-weaning mortality percentage was found to be 21.33% and Classical Swine Fever was the main cause of mortality.